Diversity of flora and the vegetation at high belt, over 1600 m alt. of the Hoang Lien national park, Lao Cai province - Tai, Vu Anh; Thin, Nguyen Nghia (Academia Journal of Biology, 2014)
The first result in this paper was list of natural vegetation types of study area according to UNESCO (1973) with 12 types in 3 classes. The second result was list and the diversity of flora at hight belt over 1600m alt. of the Hoanglien national park. 1553 species belonging to 709 genera, 189 families and 4 divisions of vascular plants were record. There are 5 new records for the flora of Vietnam (one monotype families, one monotype genus and 3 species). Magnoliophyta was most diversity phyllum; 10 richest families and 10 richest genera were listed. The third result was about the plant biogeographical elements, specially with 20.99% of species edemic for Vietnam’s flora and 4.46% of local endemic species. The lats result was plant resources, including 656 useful species (42.42%) and 58 species listed in The Red Data Book of Vietnam (1996), The Red List of IUCN (2006), CITES and The Vietnam Government Decree 32-CP (2006).